High performance concretes and applications - Shah, S. P.; Ahmad, S. H. (Edward Arnold, 1994)
Over the last decade, the use of high performance concrete has steadily increased throughout the world, particularly in the construction of tall buildings and bridges. This increased availability has been accompanied by a continuing search for improvements in the mechanical properties, methods of production and durability of this material. Inclusion of examples and case studies drawn from throughout the world. Also includes coverage of both theory and practice; and an explanation of the effect of material properties on the structural design and performance of concrete. --